2016
DOI: 10.1007/s10879-016-9328-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Examination of Changes in Psychological Flexibility Following Acceptance and Commitment Therapy for Chronic Pain

Abstract: Acceptance and commitment therapy (ACT) for chronic pain aims to improve patient functioning by fostering greater psychological flexibility. While promising, ACT treatment process research in the context of chronic pain so far has only focused on a few of the processes of psychological flexibility. Therefore, this study aimed to more comprehensively examine changes in processes of psychological flexibility following an ACT-based treatment for chronic pain, and to examine change in these processes in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 45 publications
(58 reference statements)
10
66
0
Order By: Relevance
“…Differences in measures between studies may account for these discrepancies. In a nonrandomized study of patients receiving intensive interdisciplinary ACT for chronic pain, the pre-to Average pain 3 months 6.3 (5.5, 7.1) 5.9 (5.0, 6.8) 0.19 6.5 (5.9, 7.2) 6.2 (5.5, 6.9) 0.16 9 months 6.1 (5.3, 7.0) 5.9 (5.1, 6.8) 0.10 6.4 (5.7, 7.0) 6.2 (5.5, 6.9) 0.11 Average distress 3 months 5.5 (4.7, 6.4) 5.4 (4.6, 6.1) 0.05 5.7 (5.0, 6.5) 5.6 (4.9, 6.2) 0.06 9 months 5.5 (4.7, 6.4) 5.5 (4.8, 6.3) 0.01 5.6 (4.9, 6.3) 5.6 (5.0, 6.3) 0.01 BPI pain interference 3 months 5.7 (5.0, 6.3) 6.1 (5.4, 6.7) 0.24 5.9 (5.4, 6.5) 6.2 (5.7, 6.7) 0.20 9 months 5.4 (4.8, 6.1) 6.3 (5.7, 7.0) 0.54 5.8 (5.3, 6.4) 6.4 (5.9, 6.9) 0. post-treatment effects for acceptance, decentring, and committed action were comparable to the between-groups effects observed on these variables in the current study (Scott et al, 2016). The outcome estimates reported here may be used to perform sample size calculations for a larger trial.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Differences in measures between studies may account for these discrepancies. In a nonrandomized study of patients receiving intensive interdisciplinary ACT for chronic pain, the pre-to Average pain 3 months 6.3 (5.5, 7.1) 5.9 (5.0, 6.8) 0.19 6.5 (5.9, 7.2) 6.2 (5.5, 6.9) 0.16 9 months 6.1 (5.3, 7.0) 5.9 (5.1, 6.8) 0.10 6.4 (5.7, 7.0) 6.2 (5.5, 6.9) 0.11 Average distress 3 months 5.5 (4.7, 6.4) 5.4 (4.6, 6.1) 0.05 5.7 (5.0, 6.5) 5.6 (4.9, 6.2) 0.06 9 months 5.5 (4.7, 6.4) 5.5 (4.8, 6.3) 0.01 5.6 (4.9, 6.3) 5.6 (5.0, 6.3) 0.01 BPI pain interference 3 months 5.7 (5.0, 6.3) 6.1 (5.4, 6.7) 0.24 5.9 (5.4, 6.5) 6.2 (5.7, 6.7) 0.20 9 months 5.4 (4.8, 6.1) 6.3 (5.7, 7.0) 0.54 5.8 (5.3, 6.4) 6.4 (5.9, 6.9) 0. post-treatment effects for acceptance, decentring, and committed action were comparable to the between-groups effects observed on these variables in the current study (Scott et al, 2016). The outcome estimates reported here may be used to perform sample size calculations for a larger trial.…”
Section: Discussionsupporting
confidence: 75%
“…Differences in measures between studies may account for these discrepancies. In a nonrandomized study of patients receiving intensive interdisciplinary ACT for chronic pain, the pre‐ to post‐treatment effects for acceptance, decentring, and committed action were comparable to the between‐groups effects observed on these variables in the current study (Scott et al., ).…”
Section: Discussionsupporting
confidence: 72%
“…The present results suggest that cognitive fusion is an important mediator of the relationship between PTSD and chronic pain. The results are in line with previous studies suggesting that cognitive fusion and similar processes, such as decentering and cognitive inflexibility, are related to functioning in chronic pain and separately to the severity of PTSD [27,28,30,68], and with models of PTSD which specify that the way a person processes and interprets an traumatic event plays an important role in the development and maintenance of symptoms and in response to treatment for PTSD [20,69,70]. Furthermore, the results are in accordance with a recent study where catastrophizing and fear-avoidance beliefs, other types of dysfunctional cognitive processes, have been identified as mediating factors of the relationship between PTSD and pain intensity [15].…”
Section: Discussionsupporting
confidence: 92%
“…Unauthorized reproduction of the article is prohibited. from a growing list of studies connecting processes from the theoretically-based and potentially integrative psychological flexibility model to the relationship between PTSD and chronic pain [6,33,34] and with studies connecting these processes, or other processes similar to those described in the this model, to the severity of pain and pain-related impairment, and separately to the severity of PTSD [24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…There are now relatively comprehensive tests of the role of facets of PF in improvements observed in intensive psychologically-based treatment for chronic pain (31,32). In our study on this topic we showed that improvements in acceptance, cognitive fusion, and committed action play a role both at post treatment and at a nine-month follow-up, accounting for more than 20% of the variance in improvements, particularly in social and emotional functioning (31).…”
Section: Process and Mechanism In Actmentioning
confidence: 71%